Comment on allogeneic umbilical cord-derived mesenchymal stem cell transplantation for treating chronic obstructive pulmonary disease: A pilot clinical study - Stessuk, Talita [UNESP]; Ribeiro-Paes, João Tadeu [UNESP] (Springer Nature, 2020)
In the clinical study by Le Thi Bich et al., allogeneic expanded umbilical cord-derived mesenchymal stem cells (UC-MSCs) were intravenously infused to treat patients with chronic obstructive pulmonary disease (COPD). No severe or significant adverse effects were observed, while a significant improvement in COPD patients' quality of life was reported up to 6 months. In addition, the authors argue that bone marrow-derived cells are not suitable to treat COPD based on the failureof 3 clinical trials (NCT01110252, NCT01306513, and NCT00683722). In fact, Le Thi Bich et al. and the three above-mentioned studies reported similar clinical outcomes, id est., no significant improvement in the pulmonary function of COPD patients. Therefore, since no COPD treatment involving cells either from bone marrow or umbilical cord was detrimental or provided lung regeneration in human patients, in our view, it is too early to point failures of cellular sources. Instead, it is a valuable opportunity to reflect on the poorly understood therapeutic mechanism of MSCs and the pathophysiology of COPD. In respect of cellular sources, only controlled trials with a strict comparison between different tissues might determine the suitability and efficacy of specific cell types to treat COPD. Finally, further studies are still required to determine whether and via which mechanism MSCs are able to provide structural and functional restoration of gas exchange in COPD patients.
Keywords: Cell therapy; Clinical trial; COPD; Pulmonary emphysema